PENERAPAN (PROBLEM - BASED LEARNING) KELAS VII C PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP BUDI UTOMO SURAKARTA - Aziza, Nurul; Muslimin, Edy (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
This study aims to examine how Problem-Based Learning (PBL) is implemented in the Islamic Religious Education (PAI), Identify the supporting and inhibiting factors during the implementation of PBL and to describe strategies that can be used to optimize its application in order to improve student learning outcomes. This study employs a descriptive qualitative approach, with data collected through interviews, classroom observations, and documentation. The research was conducted at SMP Budi Utomo Surakarta from October 2024 to September 2025, involving PAI teachers, the homeroom teacher, and students of Grade VII C as the research subjects. Data were analyzed through data condensation, narrative data presentation, and conclusion drawing. The findings indicate that the implementation of PBL in the PAI classroom of Grade VII C is carried out effectively and follows systematic learning stages. Supporting factors include students’ high learning motivation, interactive learning methods, the availability of textbooks and learning media, and the school’s support for innovative teaching. Meanwhile, the inhibiting factors consist of limited instructional time, differences in students’ ability to understand problems, and unequal availability of multimedia facilities in each classroom.Overall, the PBL strategy is considered effective, as it enhances student collaboration, encourages active participation, and develops critical thinking and problem-solving skills.